Feasibility of Implementation of a Parenting Intervention with Karen Refugees Resettled from Burma. (1st December 2017) - Ballard, Jaime; Wieling, Elizabeth; Forgatch, Marion
Abstract : Parents and children exposed to war and relocation have high rates of negative relational and mental health outcomes. This study tested the feasibility of implementing an adapted evidence‐based parenting intervention for contexts of trauma and relocation stress. Eleven Karen refugee caregivers from Burma participated in the intervention. Participants and a focal child completed ethnographic interviews as well as structured assessments at baseline and follow‐up. Caregivers reported changes in their teaching, directions, emotional regulation, discipline, and child compliance. Children reported changes in these areas and in positive parent involvement. Caregivers reported higher mental health distress immediately after the intervention, potentially due to increased awareness. Researchers made personalized referrals for counseling services as needed. Children reported a decrease in mental health symptoms.